Fabrication of anti-vitiligo ointment containing Psoralea corylifolia: in vitro and in vivo characterization - Hussain I; Hussain N; Manan A; Rashid A; Khan B; Bukhsh S (Dove Medical Press, 2016)
Irshad Hussain,1,2 Nisar Hussain,3 Abdul Manan,1,2 Abdur Rashid,4 Barkat Khan,5 Sattar Bakhsh5 1Department of Dermatology, 2Department of Pharmacy, SMBB Medical University, Larkana, 3Faculty of Pharmacy, Bahauddin Zakariya University, Multan, 4Drug Regulatory Authority of Pakistan, Islamabad, 5Faculty of Pharmacy, Gomal University, D.I.Khan, Pakistan Background: Vitiligo is a repugnant and odious dermatological malady of the time. It has an detrimental impact on the pigmentation of the human skin as a result of the destruction of cutaneous melanocytes. It affects 1%–2% of the population worldwide. Different therapeutic regimens have been deployed to treat vitiligo, but none of them could stand alone to be stated as a perfect cure. Recently, a change has been observed through novel experimental-designed optimization leading to the development of an anti-vitiligo ointment containing Psoralea corylifolia (PC) seed powder. Aim: The aim of this study was to explore the clinical outcomes of ointment containing powdered seeds of PC. Materials and methods: Guided by the protocol Response Surface Methodology, 13 formulations of concentration variance of permeation enhancers were prepared. The formulation fulfilling the required criteria (pH; temperature stability tests at 8°C±0.1°C, 25°C±0.1°C and 40°C±0.1°C; and the physical properties such as color, bleeding and rheology) was selected for clinical trials. Fourier transform infrared spectroscopy studies of seed powder of PC and selected formulation of the seed powder were performed. After obtaining informed consents and with prior approval of university and hospital ethical review boards, 20 patients (age range 25–65 years) were included in the present study. Formulations were applied on the affected body parts of patients, and some affected portion of the same patient was taken as control (self-control study design). The pigmentation of white spots of vitiligo was photographically evaluated before, during and after 12 weeks of treatment. Analysis of the measured values was performed using GraphPad Prism version 5 statistical software. A paired sample t-test was performed to observe variation between repigmented patches and white patches of self-control. Results: Hydrophilic ointment (10% w/w) prepared with seed powder of PC was fabricated. The ointment was found effective for small circular white lesions of vitiligo as compared to self-control. Pre- and post-treatment differences in the levels of pigmentation were statistically significant (P≤0.05). Conclusion: Ointment containing seed powder of PC could be an effective monotherapy for small circular white lesions of vitiligo. Keywords: vitiligo, leucoderma, Psoralea corylifolia, PC, puva, novel design optimization, babchi, anti-vitiligo ointment